Extreme melt events on northern James Ross Island, Antarctic Peninsula region, linked to isentropic drawdown and Foehn winds - Michael Matějka; Kamil Láska; Zdeněk Stachoň (Journal of Glaciology)
The Antarctic Peninsula (AP) and James Ross Island (JRI) region have experienced exceptionally warm spells in recent decades, leading to substantial glacier mass loss. This study investigates a sequence of three massive heat waves between November 2022 and January 2023, leading to extreme surface ablation. Their impact was examined through a wide range of in-situ atmospheric and glaciological observations on two JRI glaciers: the cirque-based Triangular Glacier and the dome-shaped Davies Dome. Furthermore, the Weather Research and Forecasting model was used with a very-high horizontal resolution of 300 m to provide insights into surface–atmosphere interactions and the synoptic- and meso-scale drivers of the exceptionally high near-surface air temperatures. The three investigated events generated total surface ablation of 1237 mm w.e. on Triangular Glacier and 271 mm w.e. on Davies Dome contributing to annual ablation ≥4 times higher than a recent mean on Triangular Glacier. A striking local variability in atmosphere–glacier energy exchange was found in the complicated topography of the northeastern AP region. A complex foehn mechanism analysis revealed that isentropic drawdown with a small contribution of latent heat release played a crucial role in enhancing leeward warming and surface melt.